Postcolonial Travel Writing: Ambivalence of Colonial Discourse in O.A Bushnell’s the Return of Lono - Kristiawan Indriyanto; Tan Michael Chandra (Wanastra: Jurnal Bahasa dan Sastra, 2023)
This paper analyzes O.A Bushnell’s the Return of Lono from postcolonial perspective, focusing on the ambivalence of colonial discourse and the resulting contradiction which ultimately undermine Western claim of superiority. This novel dramatizes the arrival of Captain Cook’s expedition on the Hawai’ian isles from the first-person perspective of Jonathan Forrest as he reminiscences of their prior expedition. The Westerners’ view of an idealized and imagined Hawai’i constructs Hawai’i as a space which is exotic and primitive while simultaneously promotes the idea of beauty and welcoming. While previously abiding on the Western paradigm which denigrates the natives as animalistic and savage Others, Forrest’s perspective unsettles this dominant thought and contextualizes the resulting ambivalence within colonial discourse. This paper employs the concept of contact zone as stated by Pratt and also the theory of colonial discourse and ambivalence as is proposed by Ashcroft et al. The finding concurs that every exertion of colonial thought will result in resistance as by nature, the colonial discourse itself is intertwined with ambivalence.